Predicting Loyalty in Malaysian Public Higher Education using Theory of Planned Behaviour - Helmie Sheha Che Azemi; Abdul Rahim Romle (STIM LASHARAN JAYA MAKASSAR, 2020)
Most of studies in business and marketing are adopting various theories to understand loyalty among customers. In the recent studies, understanding customer behaviour will help institutions to re-strategize their planning and operations to increase students’ enrolment and retention. Hence, the purpose of this study is to examine the combined factors of attitude, subjective norms, perceived behavioural control and brand loyalty which mediated by intention to loyal and fill in the gap of literature pertaining brand loyalty. The application of Theory of Planned Behaviour (TPB) has been widely used to measure individual’s behaviour, and therefore, this study is intended to adopt TPB in understanding factors that influence loyalty in higher education. The findings in this study will help to provide more explanations and insight about students’ behaviour and their loyalty simultaneously will benefit the university managers to improve their future marketing strategy of HEIs